What No Means: Indigenous Feminist Refusal to Library Extraction - Wong, Desmond (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2024)
Libraries have benefitted from the extraction of Indigenous Knowledges and cultural materials through which they have sought to complete collections. This has led Indigenous communities to distrust of research and research institutions, recognizing the deep harms and exploitation of these research practices. This article undertakes a case study of the book The Sacred Scrolls of the Southern Ojibway to reveal the ways in which extractive research, publishing, and collections practices are known to Indigenous communities and are refused by them. This discussion pursues the publication and collections history of this book through the framework of refusal, an Indigenous feminist practice that asserts Indigenous Sovereignty and care practices over Knowledge. Refusal should be viewed as a generative space (Tuck and Yang 2014a) and should be taken as an invitation for libraries to question and critically evaluate the very foundational principles of our profession and practices. This article challenges three deeply held library assumptions that are revealed through refusal: (1) that extraction is inevitable, (2) that the library is the only appropriate place to steward materials, and (3) that communities should be invested in the future of the library. The call to reconceptualize extraction through refusal is essential: libraries that do not strive to be reciprocal and transformational in their relationships with Indigenous peoples will only serve as a barrier to Indigenous resurgence. Instead, we must reconceptualize librarianship practices toward a liberatory practice.